Improving Students’ Writing Skill Through Expressive Writing At SMA Yasmu Sofifi In Pandemic Covid-19 - Kalsum Latuconsina; Sariwati Muhamad (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this research is to know the students writing skill through Applying expressive writing. This research use a Quantitative method with the population consist of first grade of senior high school of SMA YASMU SOFIFI those are consist of three classes, class X, class XI, and class XII. So, the sample of this research is class X consist 15 students as the sample. In this research, the researcher collects the data by using Pre-test, Treatment and Post-test. To analyzing the data, the researcher used Arikunto design. The result of this research showed that the students’ post-test more higher than pre-test. It can explained from the data that in Pre-test no one student got category good, there are only 4 students got category enough with the score 60-70, and there are 11 students got category good less with the score 50-60. And then the Post-test showed that there are 2 students got category good with the score 70-80, 10 students got category good enough with score 60-70. And the last is 3 students got category good less with score 50-60. It means through expressive writing can improve the students’ writing skill